1986
DOI: 10.1148/radiology.159.3.3517952
|View full text |Cite
|
Sign up to set email alerts
|

Automated breast sonography using a 7.5-MHz PVDF transducer: preliminary clinical evaluation. Work in progress.

Abstract: Breast ultrasound imaging performed with an automated machine was carried out in 89 patients, and images obtained with a conventional ceramic single-focus 4-MHz transducer and a 7.5-MHz polyvinylidene fluoride (PVDF) transducer were compared. The 7.5-MHz PVDF transducer improved overall image quality in 77% of patients and had equal penetration in 83%. It yielded greatly increased diagnostic information in 43% of 81 masses and improved visualization of calcification in 57% of 14 lesions in which calcium was vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 0 publications
0
13
0
5
Order By: Relevance
“…Commercial scanners became available in the 1970s (Maturo et al 1980). Thereafter, various different automated systems were available for breast ultrasound scanning for clinical use (Chang et al 2006;Jackson et al 1986). However, these modalities were not well accepted because of their inferior sensitivity for breast mass detection, inconvenient manipulation for examiners or discomfort for patients whose breasts had to be suspended in a water bath (W€ ohrle et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Commercial scanners became available in the 1970s (Maturo et al 1980). Thereafter, various different automated systems were available for breast ultrasound scanning for clinical use (Chang et al 2006;Jackson et al 1986). However, these modalities were not well accepted because of their inferior sensitivity for breast mass detection, inconvenient manipulation for examiners or discomfort for patients whose breasts had to be suspended in a water bath (W€ ohrle et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this disadvantage, a technology for automated scanning is being developed by trial and error. [4][5][6][7][8][9] Recently, an automated breast US system with a highresolution (8 MHz) transducer was introduced. 10 Wenkel et al 10 demonstrated the possibility of using it in the clinical setting for patients with breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in reader confidence with ABVS evaluating benign lesions was most likely the result of more diagnostic information generated by the addition of a third viewing plane, coronal. The coronal view and image information from it cannot be recreated by HHBUS (23).…”
Section: Discussionmentioning
confidence: 99%